Diagnóstico de los factores que impiden el desarrollo turístico del balneario Puerto Bajaña”, cantón Buena Fe, año 2019 - Intriago Pincay, Daylin Sofía (2020)
The purpose of this project was to identify what are the factors that prevent the development of the "Puerto Bajaña" through the collection, socialization and validation of real and concise information. The internal and external situation of the establishment could be analyzed to identify the shortcomings that were presenting to improve and potentiate this tourist destination in the canton Buena Fe. 93.63% of the people surveyed mentioned that if they usually go to the tourist resort “Puerto Bajaña” frequently, while 6.37% mentioned that they do not go to this establishment 7.59% of people like to go to taste its wonderful tilapia characteristics of the place and its main strength, 21.49% of people who conducted the survey said they like to go to the Bajaña River which is the tourist attraction of more renowned, 18.04% go for the pools of that place, 11.94% usually go for the programs or events they perform in a certain time, 9.55% like to go for the relaxed atmosphere of their cabins, 6.37% prefer not to respond to the survey, 5.04% like to go to their bar / disco to have some fun. Although it is one of the tourist centers of Buena Fe with more experience, it has neglected a bit in its corporate image, which means that it no longer has the necessary reception by citizens and its tourists. Citizens consider it a little removed from the center which makes this a problem to go, since certain motorcycle taxis (tricycles) do not want to move to that destination because they consider it very far. Make a remodeling of the facilities as they are a bit deteriorated, maintain the pools, and keep prices not so high to be able to capture the largest number of customers for the tourist attraction. The Municipal GAD should be requested that one of the bus lines has its route to the "Puerto Bajaña" so that access to the establishment becomes much easier.